Long Non-coding RNAs in Traumatic Brain Injury Accelerated Fracture Healing - Guo, Guoning; Gou, Yajun; Jiang, Xingyu; Wang, Shuhong; Wang, Ruilie; Liang, Changqiang; Yang, Guang; Wang, Tinggang; Yu, Anyong; Zhu, Guoyan (Frontiers in Surgery, 2021)
It is commonly observed that patients with bone fracture concomitant with traumatic brain injury (TBI) had significantly increased fracture healing while the underlying mechanisms were not fully revealed. Long non-coding RNAs (lncRNAs) were known to playing complicated roles in bone homeostasis while their role in TBI accelerated fracture was rarely reported. The present study was designed to determine the role of lncRNAs in TBI accelerated fracture via transcriptome sequencing and further bioinformatical analysis. Blood samples from 3 fracture-only patients, 3 fracture concomitant with TIB patients, and 3 healthy controls were harvested and were subsequently subjected to transcriptome lncRNAs sequencing. Differentially expressed genes were identified, and pathway enrichment was performed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. High-dimensional data portraying by self-organizing map (SOM) machine learning was applied to further interpret the data. A xCell method was then used to predict cellular behavior in all samples based on gene expression profiles and a lncRNA-cell interaction network was generated. A total of 874 differentially expressed genes were identified, of which about 26% were lncRNAs. Those identified lncRNAs were mainly enriched on traumatic brain injury-related and damage repair-related pathways. SOM analyzes revealed that those differentially expressed lncRNAs could be divided into three major module implications and were mainly enriched on transcriptional regulation and immune-related signal pathways, which promote us to further explore cellular behaviors based on differentially expressed lncRNAs. We have predicted that basophils, CD8+ T effector memory cells, B cells, and naïve B cells were significantly down-regulated while microvascular endothelial cells were predicated significantly up-regulated with TBI/Fr group was the lowest or highest, respectively. ENSG00000278905, ENSG00000240980, ENSG00000255670, and ENSG00000196634 were the most differentially expressed lncRNAs that related to all changes of cellular behavior. The present study has revealed for the first time that several critical lncRNAs may participate in TBI accelerated fracture potentially via regulating cellular behaviors of basophils, cytotoxic T cells, B cells, and endothelial cells.